Characterization of the prostate cancer susceptibility gene KLF6 in human and mouse prostate cancers. Issue 2 (10th July 2012) - Chiam, Karen; Ryan, Natalie K.; Ricciardelli, Carmela; Day, Tanya K.; Buchanan, Grant; Ochnik, Aleksandra M.; Murti, Krisna; Selth, Luke A.; ,; Butler, Lisa M.; Tilley, Wayne D.; Bianco‐Miotto, Tina
Abstract BACKGROUND Krüppel‐like factor (KLF) 6 is a candidate tumor suppressor gene in prostate cancer, but the mechanisms contributing to its loss of expression are poorly understood. We characterized KLF6 expression and DNA methylation status during prostate tumorigenesis in humans and mice. METHODS KLF6 expression was assessed in matched human non‐malignant (NM) and tumor prostate tissues (n = 22) by quantitative real‐time PCR (qPCR) and in three independent human prostate cancer cohorts bioinformatically. QPCR for KLF6 expression and methylation‐sensitive PCR (MSP) were performed in human prostate LNCaP cancer cells after 5‐aza‐2′‐deoxycytidine treatment. Klf6 protein levels and DNA promoter methylation were assessed in TRansgenic Adenocarcinoma of Mouse Prostate (TRAMP) tumors by immunohistochemistry and MSP, respectively. RESULTS KLF6 splice variants expression was increased (P = 0.0015) in human prostate tumors compared to NM tissues. Overall, KLF6 was decreased in metastatic compared to primary prostate cancers and reduced expression in primary tumors was associated with a shorter time to relapse (P = 0.0028). Treatment with the demethylating agent 5‐aza‐2′‐deoxycytidine resulted in up‐regulation of KLF6 expression (two‐fold; P = 0.002) and a decrease in DNA methylation of the KLF6 promoter in LNCaP cells. Klf6 protein levels significantly decreased with progression in the TRAMP model of prostate cancer (P < 0.05), but there was no difference in Klf6 promoter methylation. CONCLUSION KLF6 expression was decreased in both clinical prostate cancer and the TRAMP model with disease progression, but this could not be explained by DNA methylation of the KLF6 promoter. Prostate 73: 182–193, 2013. © 2012 Wiley Periodicals, Inc.